Report of proceedings at a meeting of the Hudson's Bay Company [electronic resource] : held at the company's house in Fenchurch Street, on Wednesday, March 24th, 1869; the Right Honourable Sir Stafford Henry Northcote, bart., M.P., in the chair. - Hudson's Bay Company. ([London? : s.n.], 1869)
Discussion of the cession of Hudson's Bay Company territories to Canada. Electronic reproduction. Mode of access: Internet. 44